A Survey of Imprinted Gene Expression in Mouse Trophoblast Stem Cells. Issue 5 (1st May 2015) - Calabrese, J Mauro; Starmer, Joshua; Schertzer, Megan D; Yee, Della; Magnuson, Terry
Abstract: Several hundred mammalian genes are expressed preferentially from one parental allele as the result of a process called genomic imprinting. Genomic imprinting is prevalent in extra-embryonic tissue, where it plays an essential role during development. Here, we profiled imprinted gene expression via RNA-Seq in a panel of six mouse trophoblast stem lines, which are ex vivo derivatives of a progenitor population that gives rise to the placental tissue of the mouse. We found evidence of imprinted expression for 48 genes, 31 of which had been described previously as imprinted and 17 of which we suggest as candidate imprinted genes. An equal number of maternally and paternally biased genes were detected. On average, candidate imprinted genes were more lowly expressed and had weaker parent-of-origin biases than known imprinted genes. Several known and candidate imprinted genes showed variability in parent-of-origin expression bias between the six trophoblast stem cell lines. Sixteen of the 48 known and candidate imprinted genes were previously or newly annotated noncoding RNAs and six encoded for a total of 60 annotated microRNAs. Pyrosequencing across our panel of trophoblast stem cell lines returned levels of imprinted expression that were concordant with RNA-Seq measurements for all eight genes examined. Our results solidify trophoblast stem cells as a cell culture-based experimental model to study genomic imprinting, and provide a quantitative foundation upon which to delineate mechanisms by which the process is maintained in the mouse.